Evaluation of paraffin wax and poly(3-hydroxybutyrate-co-3-hydroxyhexanoate) blend patch for tissue engineering - Yildirim, Meryem Akkurt; Demirbilek, Murat; Turkoglu, Nelisa (TAYLOR & FRANCIS LTD, 2021)
In the study, we aimed to develop a multipurpose tissue patch for the repairment of various tissue defects. Poly (3-hydroxybutyrate-co-3-hydroxyhexanoate) (PHBHHx) was blended with paraffin wax, and the chemical composition of the membranes was determined by the FTIR and RAMAN spectroscopy. The surface area of the PHBHHx and PHBHHx/Paraffin wax were determined as (38,79 m(2)/g) and (81,108 m(2)/g), respectively. The DMA and DSC results revealed that blending with paraffin wax, increased the percentage of elongation of the PHBHHx membrane by 7,6% and reduced the modulus of elasticity. While the elongation at break of PHBHHx tissue patch was 22,463% (standard error = +/- 2,476), addition of Paraffin wax increased the value to 30,038% (standard error = +/- 7,228). The antioxidant capacity significantly increased and p53/TP53 levels decreased after blending with paraffin. In conclusion, PHBHHx/paraffin wax blend patches can be considered as a promising biomaterial due to their high cell adhesion capacity depending on its increased surface area, fine anti-oxidant properties, and appropriate mechanical properties.
Keywords: Poly (3-hydroxybutyrate-co-3-hydroxyhexanoate); paraffin wax; tissue patch; MESENCHYMAL STEM-CELLS; MECHANICAL-PROPERTIES; PHYSICAL-PROPERTIES; SCAFFOLDS; BIODEGRADATION; PROLIFERATION; BIOMATERIALS; PHBHHX; FILMS; POLYHYDROXYALKANOATES; Materials Science